Determinan Green Accounting terhadap Sustainable Development pada Perusahaan Pertambangan yang Terdaftar di BEI - Linda Arisanty Razak; Wahyuni; Nur Azizah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study examines the effect of green accounting as measured by environmental performance, environmental costs, and environmental disclosures on sustainable development in mining companies listed on the Indonesia Stock Exchange in 2017-2021.Â Determination of the sample was carried out by purposive sampling in order to obtain 15 companies.Â The type of data used in this study is secondary data obtained from the annual reports of mining companies listed on the Indonesia Stock Exchange for 2017-2021. The tests conducted in this study show that green accounting variables, as measured by environmental performance, do not affect sustainable development in mining companies.Â This is because several mining companies did not optimally implement the environmental performance of mining companies in 2017-2021, and several mining companies still need to appreciate environmental awareness. Environmental costs do not affect sustainable development in mining companies. This occurs because the environmental costs incurred by mining companies are still low and not in line with the environmental damage caused. Meanwhile, the green accounting variable, measured by environmental disclosure, significantly affects sustainable development in mining companies. This happens because mining companies have made environmental disclosures in their annual reports.